Recent Advances of Biodiesel Production Using Ionic Liquids Supported on Nanoporous Materials as Catalysts: A Review - Gholami, Ali; Pourfayaz, Fathollah; Maleki, Akbar (Frontiers in Energy Research, 2020)
For the last two decades, the biodiesel attracted increasing attention as a promising biofuel to replace fossil diesel. However, the non-recyclability of homogeneous alkali catalysts and waste generation due to subsequent water washing remained as one of the major drawbacks of the biodiesel production process in the industry. Ionic liquids are one of the best alternatives to replace alkali catalysts owing to their unique properties such as non-volatility, excellent solubility for various organic and inorganic materials, structure tunability, environment-friendliness, and wide liquid temperature. However, high viscosity and difficult recovery have limited their application. Recently, heterogenization of ionic liquids on solid supports has been proposed to circumvent these issues. Among these solids, nanoporous materials have shown great potential in providing stable supports with high porosity and specific surface area. This paper reviews the recent developments in designing ionic liquids deposited on nanoporous materials as catalysts for biodiesel production. The emphasis was on the application of this type of catalysts for the optimization of reaction conditions. Moreover, challenges and opportunities for improving the overall production process in the presence of these catalysts were discussed. Despite that high biodiesel yields were obtained over many of nanoporous material-supported ionic liquids, their significantly higher cost compared to the conventional catalysts remained a major challenge. This issue can be overcome by employing less expensive cations and anions, increasing the loading amount of ionic liquids, and improving catalyst reusability in future studies.